2019
DOI: 10.5334/ijic.4632
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Integrated Care on Patient-Related Outcomes Among Older People – A Systematic Review

Abstract: Introduction: The growing number of older adults with multiple needs increases the pressure to reform existing healthcare systems. Integrated care may be part of such reforms. The aim of this systematic review was to identify important patient-related outcomes of integrated care provided to older adults. Methods: A systematic search of 5 databases to identify studies comprising older adults assessing hospital admission, length of hospital stay, hospital readmission, pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
83
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(84 citation statements)
references
References 55 publications
(120 reference statements)
0
83
0
1
Order By: Relevance
“…[1][2][3] Studies like these stick out, even in an equivocal evidence base that cannot agree whether integrated care initiatives can reduce the use or cost of services in the community and in hospitals. [4][5][6][7] The curious studies we highlight raise questions about why such unexpected results are still being found decades into the integrated care journey in England, and whether the aims of integration, specifically surrounding reducing hospital admissions and improving system efficiency, will ever be consistently achieved. In this paper, we examine potential flaws in the design, delivery and evaluation of integrated care programmes and make recommendations to improve how integrated care initiatives are planned and evaluated.…”
Section: Introductionmentioning
confidence: 97%
“…[1][2][3] Studies like these stick out, even in an equivocal evidence base that cannot agree whether integrated care initiatives can reduce the use or cost of services in the community and in hospitals. [4][5][6][7] The curious studies we highlight raise questions about why such unexpected results are still being found decades into the integrated care journey in England, and whether the aims of integration, specifically surrounding reducing hospital admissions and improving system efficiency, will ever be consistently achieved. In this paper, we examine potential flaws in the design, delivery and evaluation of integrated care programmes and make recommendations to improve how integrated care initiatives are planned and evaluated.…”
Section: Introductionmentioning
confidence: 97%
“…Hopman et al 41 ; Kaufman et al 42 ; Liljas et al 26 ; Looman et al 43 ; Mitchell et al 45 model. Furthermore, H ebert et al 48 argue that the correlation of implementation measures and effects "will help to decrease the "black box" effect of health services intervention and to avoid a "type 3 error" in measuring the effect of an intervention that has not really been or was not sufficiently implemented" (p. 10).…”
Section: Measurement Of Effects (N ¼ 8)mentioning
confidence: 99%
“…Reviews on effects revealed five main categories of indicators i) effects on the patient's health, 26,[40][41][42][43]45 ii) effects on caregivers and professionals, 40,43 iii) effects on the integration process, 42,43,45 iv) effects on health care usage 26,[41][42][43] and v) effects on service costs or resource use. 40,41,43,45 Although these reviews provide many outcome indicators, it is not clear which indicators are best used in various conditions.…”
Section: Choosing the Right Types Of Effects To Measurementioning
confidence: 99%
See 1 more Smart Citation
“…To address this challenge, the integration of health services has been promoted in many countries. However, most studies deal with integrated care interventions in a local setting and include a rather limited number of people [8][9][10][11][12]. It is well known that such innovations and programmes often have difficulties scaling up to provide sustainable, long-term interventions on a societal, whole-system level [13][14][15].…”
mentioning
confidence: 99%